Simplified automatic measurements of blood flow by the ultrasonic pulse doppler method - NOWICKI, Andrzej (Archives of Acoustics, 1979)
A new simplified method of measurement and recording of time averaged blood flow profiles in superficial arteries in man, using an ultrasonic pulse flowmeter IMP-30, is described. The results of model investigations of flows in tubes, and subsequently preliminary results of measurements in carotid and femoral arteries are discussed.